Pemberdayaan Remaja Melalui Inovasi Pembuatan Permainan Congkak Berbasis Digital Pada Komunitas Permainan Tradisional Di Desa Tanjung Rejo Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Rosramadhana Rosramadhana; Sudirman Sudirman; Zulaini Zulaini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Traditional games are one of the cultural products possessed by the Indonesian people and have been cultured from one generation to the next. Introducing traditional games can have a positive impact due to the meaning of educational values ​​characterized by Indonesian culture. In Indonesia, traditional games have characteristics and depend on the culture of various ethnicities that preserve these traditional games. In Indonesia, the traditional game that is preserved between them is arrogant. This game has different names from various ethnic groups in Indonesia. In Java this game is better known as dhakon, while in Sumatra it is called congkak. The method of implementation in the activities carried out is to find alternative solutions to partner problems, especially in empowering adolescents through four stages, namely planning, organization, actualization, and supervision. The implementation of this activity program resulted in the creation of digital-based arrogant game innovations such as digital posters, animation, arrogant game innovation and the creation of a youtobe account. This activity empowers adolescents, especially in strengthening local culture and cultural values ​​through innovative traditional games and honing youth creativity through appropriate technology.